Bone-targeted methotrexate–alendronate conjugate inhibits osteoclastogenesis in vitro and prevents bone loss and inflammation of collagen-induced arthritis in vivo. (1st January 2018) - Xie, Zi'ang; Liu, Guanxiong; Tang, Pan; Sun, Xuewu; Chen, Shuai; Qin, An; Zhu, Peizhi; Zhang, Jianfeng; Fan, Shunwu
Abstract: Rheumatoid arthritis (RA), a disease that causes joint destruction and bone erosion, is related to osteoclast activity. RA is generally treated with methotrexate (MTX). In this study, a MTX–Alendronate (ALN) conjugate was synthesized and characterized. The conjugate dramatically inhibited osteoclast formation and bone resorption compared with MTX and ALN used alone or in combination. Due to the characteristics of ALN, the MTX–ALN conjugate can adhere to the exposed bone surface and enhance drug accumulation in the pathological region for targeted therapy against osteoclastogenesis. Additionally, MTX was rapidly released in the presence of lysozyme under mildly acidic conditions, similar to inflammatory tissue and osteoclast-surviving conditions, which contributes to inflammatory inhibition; this was confirmed by the presence of pro-inflammatory cytokines. Our study highlights the use of the MTX–ALN conjugate as a potential therapeutic approach for RA by targeting osteoclastogenesis.